Provided that g : R -> R is such that g(x) = x^3 + 3·x^2 + 3·x everywhere, and that id : R -> R is such that id(x) = x everywhere, find all f : R -> R such that f°g = id. This is a well-defined search, since g is surjective. As is, f is a left-inverse of g. For such a left-inverse to exist, g must be injective. The injectivity of g would normally be tested by looking at monotonicity and continuity, and you would test for monotonicity by looking at the critical points. However, here, notice that x^3 + 3·x^2 + 3·x = (x + 1)^3 - 1, so if a, b : R -> R are such that a(x) = x - 1, b(x) = x^3, then g = a°b°a^(-1), and here, notice that a, b, a^(-1) are all injective and surjective, and thus bijective. Hence g is indeed injective, and in fact, bijective, which implies f exists, and is unique, and it also implies that f°g = g°f, meaning that (f(x) + 1)^3 - 1 = x everywhere. This simplifies the task significantly, and we can immediately conclude f(x) = cbrt(x + 1) - 1 everywhere. Q. E. D.
@angelmendez-rivera3512 жыл бұрын
Note: it actually is important to establish that g is surjective. If g were not surjective, then f *would not* be unique. For instance, let us replace the equation f(x^3 + 3·x^2 + 3·x) = x everywhere with f(arctan(x)) = x everywhere. Here, g : R -> R is such that g(x) = arctan(x) everywhere, and so we want to find all f such that f°g = id. g is injective, but not surjective, with range(g) = (-π/2, π/2). Why is this important? Because we can conclude f(x) = tan(x) for all x in (-π/2, π/2), but you *cannot* conclude f(x) = tan(x) everywhere. As an example, let f0(x) = tan(x) for all x in (-π/2, π/2), but f0(x) = 0 for all other x. Then, even though f is not equal to f0, f0 also satisfies the equation, in that f0°g = id in this case. Indeed, f0(arctan(x)) = x everywhere. Therefore, there are at least two functions satisfying the equation. In fact, there are infinitely many. Consider an arbitrary h : R\(-π/2, π/2) -> R. Let f[h] : R -> R be such that f[h](x) = tan(x) for all x in (-π/2, π/2), f[h](x) = h(x) for all other x. Then, for all such h, f[h]°g = id is true, and f[h] is distinct for each h. This means there are card(R)^card(R\(-π/2, π/2)) = Beth(1)^Beth(1) = 2^Beth(1) = Beth(2) functions that solve the equation. This can be made completely general. In the most general situation, consider some given, known function g : R -> R. The task is to find all f : R -> R such that f°g = id, where id : R -> R such that id(x) = x everywhere, a.k.a find every left inverse of g. Let g^λ : range(g) -> R be such that g^λ(g(x)) = x everywhere. g^λ is well-defined, since there is only one function satisfying this property. Consider an arbitrary function h : R ange(g) -> R. Now, let f[h] : R -> R such that f[h](x) = g^λ(x) for all x in range(g), f[h](x) = h(x) otherwise. Thus, for all such h, f[h]°g = id, and for each distinct h, f[h] is distinct as well. The number of distinct f[h] that exist is equal to card(R)^card(R ange(g)) = Beth(1)^card(R ange(g)). In the special case that g is surjective, range(g) = R, so R ange(g) = {}, meaning that card(R ange(g)) = 0, so Beth(1)^card(R ange(g)) = Beth(1)^0 = 1, and so f is unique. Otherwise, there are infinitely many f: at least Beth(1) of them, and if R ange(g) is uncountable, then exactly Beth(2) of them. Of course, this all assumes g is injective. If g is not injective, then f simply does not exist, and there is nothing else to discuss. So, in summary: if g is not injective, then there are 0 functions f satisfying the equation; if g is injective, and surjective, then there is 1 function f satisfying the equation; if g is injective, and not surjective, and range(g) is cocountable in R, then there are Beth(1) functions satisfying the equation; if g is injective, and not surjective, and range(g) is not cocountable in R, then there are Beth(2) functions satisfying the equation. In this video, though, g is surjective, so f is unique, and in fact, f = g^(-1), keeping it simple.
@SyberMath2 жыл бұрын
Wow! You are amazing, Angel!
@helene88542 жыл бұрын
Chapeau.
@morteza32682 жыл бұрын
This is how I solved it: we know f(g(x))=x so g(x)=f^(-1)(x) That is, it is the inverse of the function f y=ax³+bx²+cx+d If b²-3ac=0 If this condition is met, the inverse of the function is equal to : y^(-1)=[(x-d)/a+(b/3a)³]⅓-(b/3a) f(x)=cbrt((x+1)-1
@vishalmishra30462 жыл бұрын
*General strategy* set y = x^3 + 3x^2 + 3x and then calculate x in terms of y. y = (x+1)^3 - 1 => x = (y+1)^(1/3) - 1 So, using x instead of y, f(x) = (x+1)^(1/3) - 1 *Simple* Right ?
@GirishManjunathMusic2 жыл бұрын
Given: f(x³ + 3x² + 3x) = x To find: f(x) Setting x³ + 3x² + 3x = y: Adding 1 to both sides: x³ + 3x² + 3x + 1 = y + 1 (x + 1)³ = y + 1 Raising both sides to the ⅓ power: x + 1 = (y + 1)↑⅓ x = (y + 1)↑⅓ - 1 Thus: f(y) = (y + 1)↑⅓ - 1
@TeslaEdits_2 жыл бұрын
Nice
@chixenlegjo2 жыл бұрын
I took the derivative to look for any extrema. After noticing that there was exactly one horizontal tangent and that the a value of the cubic was 1, I knew it would be in the form f(x)=cbrt(x-h)+k where (k,h) is the point at which the horizontal tangent intersects the cubic. Finding this was easy due to my first step.
@benheideveld46172 жыл бұрын
The equation f(g(x)) = x is asking the inverse function of g(x). I would not call that a functional equation. A functional equation requires f to occur at least twice and not of a constant like f(1).
@SyberMath2 жыл бұрын
Hey! Long time, no see! 😁
@angelmendez-rivera3512 жыл бұрын
*A functional equation equation requires f to occur at least twice...* According to who?
@angelmendez-rivera3512 жыл бұрын
Also, strictly speaking, the equation is only asking for a left-inverse. It is conceivable that not only multiple left-inverses could exist, if no right-inverses exist, but also that none may exist at all. g is bijective, and that is really the key observation to solve this equation uniquely. However, g could have been chosen so that it was injective, but not surjective on R, or that it was not injective to begin with. So, the problem is not as simple as you are dismissing it to be. Syber kept it easy by choosing g to be bijective, but strictly speaking, you still have to at least state that explicitly as a premise in your proof, and explain why that matters. In this case, g being bijective means that f°g = g°f = id, and so we can rewrite f°g = id as g°f, meaning that (f(x) + 1)^3 - 1 = x everywhere, and now the solution is obvious. You could not assert this if g was not injective, though. You also could not assert f is unique without indicating g is surjective (if g is not surjective, then f is definitely not unique).
@benheideveld46172 жыл бұрын
@@angelmendez-rivera351 Thank you for your kind and thorough stipulations. It is this kind of interaction with people more knowledgeable than me that makes it worthwhile to participate in a group like this. I notice that most people don’t like to be wrong about what they say. I love being wrong sometime, that is when I learn. I studied physics (BSc & MSc) and I notice this my attitude is a scientist’s attitude.
@moeberry82262 жыл бұрын
The Master has done it again. Bravo.
@SyberMath2 жыл бұрын
Aww, thanks for the kind words!!! 🥰🤗💖
@ИльхамАбдуллаев-ь6й2 жыл бұрын
Nice problem with original Solution .Thank you .Bravooo 👍👍👍👍👍👍👏
@SyberMath2 жыл бұрын
You are welcome
@mcwulf252 жыл бұрын
Once I saw that the LHS was a difference of cubes the rest was easy. A general solution of f(cubic in x) = X is much more complex.
@williamwilliam49442 жыл бұрын
I feel like the question requires more parameters. There are infinite functions that solve this expression. For example, f:Pn(R) -> P1(R) can be defined as f(a + bx + cx² + dx³ + ...) = (1/3)bx and we are done
@GourangaPL2 жыл бұрын
6:21 in Poland we call it "shooting a fly with a cannon"
@SyberMath2 жыл бұрын
Wow! That's cool!
@wonghonkongjames44952 жыл бұрын
Mr, it's just an inverse function of the said expresion. Namely, take the cubic root of ((...)十1),and then -1. The correct wordings are therefore f(y)=(cu rt(y十1))-1,when y=..., f(y)=x.
@juanmolinas2 жыл бұрын
Hi Syber! I spent some time trying but I fell into the temptation to see how you solve it XD
@SyberMath2 жыл бұрын
Hi Juan! Some temptations are not that bad after all! 😁🤩
@tontonbeber45552 жыл бұрын
Let's try something like ... y = x3 + 3x2 + 3x = (x+1)3 -1 (y+1) = (x+1)3 f(y) = x = cubicroot(y+1) -1
@edreds21452 жыл бұрын
Sup! One question, why, in the minute 1:56, you can move “y” to the left side? I didn’t understand
@manioqqqq2 жыл бұрын
2:29 YOU SHOULDN'T HAVE GIVEN ME THIS POWER!!!
@SyberMath2 жыл бұрын
Too late! 😜
@Ghaith77022 жыл бұрын
"remind myself to slow down" hhh nice
@SyberMath2 жыл бұрын
😜
@georgepaidas11322 жыл бұрын
That's really one of your best problems. Great!!!!
@SyberMath2 жыл бұрын
Glad you think so! The fact that it's homemade makes me more proud 😉🥳
@science_nepal_lover2 жыл бұрын
@@SyberMath just multiply both sides by 0 Duh
@jyl1232 жыл бұрын
@@science_nepal_lover you are so smart 🤓
@notlin19762 жыл бұрын
Today I viewed both solutions... Very, very good... 🇧🇷🇧🇷🇧🇷🇧🇷🇧🇷🇧🇷🇧🇷🇧🇷🇧🇷🇧🇷🇧🇷🇧🇷
@SyberMath2 жыл бұрын
Thank you! 💖
@giuseppemalaguti4352 жыл бұрын
f(x) =sqrt3(1+x)-1
@mathswan16072 жыл бұрын
f(x)= cube root (x+1)-1
@figoprovenza95132 жыл бұрын
Nice video👍🏻
@dopo83332 жыл бұрын
Easy-peasy. :)
@kimi20F1c2 жыл бұрын
Just send every Polynomial to the Polynomial x.
@shmuelzehavi49402 жыл бұрын
Another way: The given equation: f(x^3 + 3x^2 + 3x) = x We denote: u = x^3+3x^2+3x and we have to express x as a function of u . Therefore, we have to solve for x the equation: x^3 + 3x^2 + 3x = u Or: x^3 + 3x^2 + 3x + 1 = u + 1 Or: (x + 1)^3 = u + 1 Or: x + 1 = ∛(u + 1) ⟹ x = ∛(u + 1) - 1 Therefore we obtain: f(u) = ∛(u + 1) - 1 Or: f(x) = ∛(x + 1) - 1
@elmurazbsirov76172 жыл бұрын
Bakıdan salamlar.Əla həll etdiniz.
@SyberMath2 жыл бұрын
Çox sağ ol! Amerika Birləşmiş Ştatlarından salamlar!
@lesindorf-934videos2 жыл бұрын
For what?
@boraned2 жыл бұрын
Abi ingilizcen gayet gelişmiş. Daha demin 1 yil onceki videonu izliyodum, türk oldugun hayvan kadar anlasiliyordu
@SyberMath2 жыл бұрын
Saol! 😁😂
@boraned2 жыл бұрын
@@SyberMath zekani harbiden apprieciateliyorum abi. content cok kafa aciyor, cok ilgi cekici ayni zamanda.
@hadibendj97162 жыл бұрын
It's an incredible solution sir thank's very much, i like your channel.
@SyberMath2 жыл бұрын
Thanks and welcome! 🥰
@m_th_m_t_cs2 жыл бұрын
I found 'f' in front of (
@clearmist12 жыл бұрын
This is dumb the answer is negative 1. I looked at that seeing three larger x values = x. so it must be negative. Seen negative one was a candidate to work solved it using negative one as x and the answer comes out as negative one.
@vuqou26642 жыл бұрын
6/10/2022
@rpradhan5002 жыл бұрын
-1
@theblinkingbrownie46542 жыл бұрын
f(x)=0
@barakathaider63332 жыл бұрын
👍
@carolingian57362 жыл бұрын
Zero
@rushhourgaming2 жыл бұрын
No, I can't
@andirijal90332 жыл бұрын
sirr are you from Ukraina ?
@SyberMath2 жыл бұрын
No, I'm not
@user-qawsedrftgyhujikolp102 жыл бұрын
同じことやん
@vladimirkaplun57742 жыл бұрын
Boring
@azizhankaya86942 жыл бұрын
are you türk?
@SyberMath2 жыл бұрын
Senden kaçmıyor abi hiçbir şey! 😜
@maaday2 жыл бұрын
@@SyberMath bazen çıkmış sorular bazen de aksan çok hafif belli belirsiz buradayım diyor. Elinize aklınıza sağlık başarılarınızın devamını dilerim